Metastatic signet-ring cell carcinoma of the urinary bladder: A novel management approach to a rare tumour - Pugashetti, Neil; Yap, Stanley A.; Lara Jr., Primo N.; Gandour-Edwards, Regina; Dall'Era, Marc (Canadian Urological Association Journal, 2015)
Primary signet-ring cell carcinoma (SRCC) of the urinary bladder, a variant of adenocarcinoma, is exceedingly rare and as a result no gold standard exists for its management. We report a case of primary SRCC of the bladder with recurrent metastases; we utilized an innovative diagnostic approach and the patient exhibited a treatment response to palliative FOLFOX-6 chemotherapy.